(untitled) (Research, Society and Development, 2021)
The objective of this paper is to reflect on the conditions and challenges faced by adolescents in freedom deprivation in Brazil regarding the realization of health rights, from the creation of the National Policy for complete attention in Health of adolescents in conflict with the Law, created in 2004 and reworked and amplified in 2014. In order to achieve that, a bibliographical and documental research was exploratory conducted, regarding the right and access to complete attention in health of adolescents in freedom deprivation. The documents and articles evoked in the text demonstrate a history of denial of the right to health to institutionalized adolescents. It was concluded that after almost two decades since the creation of the referred policy, the difficulties to assure the right to health of adolescents in conflict with the Law still persist in virtually all national territory, be it due to challenges, subjectivities and complexities that evolve the socioeducational work, be it for the interests and political priorities. Finally, it is worth to note that the Law itself does not assure rights, it is imperative the ethical and political committment of society to consolidate socioeducation as an educational, inclusive and restorative public policy.